Strengthening Systems to Support Mothers in Infant and Young Child Feeding at Scale. Issue 3 (September 2013) - Sanghvi, Tina; Martin, Luann; Hajeebhoy, Nemat; Abrha, Teweldebrhan Hailu; Abebe, Yewelsew; Haque, Raisul; Tran, Ha Thi Thu; Roy, Sumitro
Background: Systems strengthening is essential for implementation of large-scale nutrition interventions, including infant and young child feeding (IYCF), since rapid geographic expansion places additional burdens on service delivery systems. Objective: To document approaches for building capacity and supporting programs to scale up IYCF counseling in three different country contexts. Methods: Situational assessments, stakeholder consultations, formative research, household and frontline health worker surveys, other related studies, and program monitoring in three countries identified gaps and opportunities for strengthening IYCF service delivery. Results: Variations in program platforms, level and roles of service providers, places of service delivery, community factors, and the needs of managers and frontline workers influenced the intervention mix used for strengthening IYCF services. The programs ranged from a highly structured and standardized package of IYCF counseling services in Vietnam delivered through government health facilities to counseling delivered at the doorstep by incentivized nongovernmental organization volunteers in Bangladesh. In Ethiopia, government health extension workers based at health posts conducted outreach visits with support from volunteers. Conclusions: Guidelines and standards of care, training, job aids, supportive supervision, incentives, and monitoring data can enhance performance and strengthen systems for delivering IYCF counseling services in the community or at health facilities. Leadership, financing, partnerships, and logistics support are essential to support large-scale implementation of the IYCF counseling package in diverse service delivery environments.